Coevolution of Genome Architecture and Social Behavior. (September 2019) - Rubenstein, Dustin R.; Ågren, J. Arvid; Carbone, Lucia; Elde, Nels C.; Hoekstra, Hopi E.; Kapheim, Karen M.; Keller, Laurent; Moreau, Corrie S.; Toth, Amy L.; Yeaman, Sam; Hofmann, Hans A.
Abstract : Although social behavior can have a strong genetic component, it can also result in selection on genome structure and function, thereby influencing the evolution of the genome itself. Here we explore the bidirectional links between social behavior and genome architecture by considering variation in social and/or mating behavior among populations (social polymorphisms) and across closely related species. We propose that social behavior can influence genome architecture via associated demographic changes due to social living. We establish guidelines to exploit emerging whole-genome sequences using analytical approaches that examine genome structure and function at different levels (regulatory vs structural variation) from the perspective of both molecular biology and population genetics in an ecological context. Highlights: Social behavior has a genetic basis but can also affect genome structure and function. As a consequence, social behavior can influence the evolution of the genome itself. We discuss bidirectional links between social behavior and genome architecture. We argue that social living can influence genome architecture via demographic processes. We propose guidelines for examining genome structure and function at different levels.